The impact of the institutional absorptive capacity on public debt in aid-recipient MENA countries - Sidani, Ola; Taher, Hanadi; Houshaimi, Maggie (Edelweiss Applied Science and Technology, 2024)
Aid efficiency is contingent to the institutional framework of an economy, including governance structure and other contextual factors that affect the absorptive capacity for aid. The institutional absorptive capacity is thus a critical factor influencing fiscal imbalances and public debt levels in aid-recipient in developing economies. This paper examines the impact of the institutional absorptive capacity for aid on public debt in 12 aid-recipient MENA countries over the period 2012-2022. By integrating governance indicators with contextual non-macroeconomic elements, this paper defines the non-linear relationship between the institutional absorptive capacity and debt-to-GDP. It proposes a novel measurement for the institutional absorptive capacity, using the Principal Components Analysis method to compile the World Bank’s worldwide governance indicators along with the human development index (HDI), government digitization, and access to electricity. It proposes using system one-step GMM estimation model which caters for all drawbacks of other estimation techniques. Findings show a strong negative impact of the institutional absorptive capacity for aid on public debt. The paper provides evidence-based intuition for policymakers in the MENA region, underscoring the importance of governance-driven reforms as a pathway to minimize continuous dependency on external borrowing and ensure sustainable public debt.